Peran Kebijakan Struktur Modal Terhadap Profitabilitas pada Perusahaan Properti dan Real Estate - Setiawan, Setiawan (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
Property and real estate sector companies are showing increasing optimism. This is driven by the increasing public demand for private housing. A market that continues to grow is a good prospect for property and real estate sector companies. However, it is undeniable that the property and real estate sector companies are capital-intensive companies, so a large amount of capital is required. One alternative is the use of debt policy. If the use of debt is appropriate, of course, it can provide large returns in the form of company profits. This study seeks to explore the role of capital structure in profitability in property and real estate sector companies. The data used is secondary data obtained from the financial statements of property and real estate sector companies listed on the Indonesian Stock Exchange in 2016-2019. The results show that the capital structure policy as proxied by the Debt to Assets Ratio (DAR) has a positive effect on company profitability as proxied by Return on Equity (ROE) in relatively smaller and younger companies. While the Debt to Equity Ratio (DER) has no effect on ROE.